Spatially-directed cell migration in acoustically-responsive scaffolds through the controlled delivery of basic fibroblast growth factor. (1st September 2020) - Lu, Xiaofang; Jin, Hai; Quesada, Carole; Farrell, Easton C.; Huang, Leidan; Aliabouzar, Mitra; Kripfgans, Oliver D.; Fowlkes, J. Brian; Franceschi, Renny T.; Putnam, Andrew J.; Fabiilli, Mario L.
Abstract: Hydrogels are commonly used in regenerative medicine for the delivery of growth factors (GFs). The spatial and temporal presentations of GFs are critical for directing regenerative processes, yet conventional hydrogels do not enable such control. We have developed a composite hydrogel, termed an acoustically-responsive scaffold (ARS), where release of a GF is non-invasively and spatiotemporally-controlled using focused ultrasound. The ARS consists of a fibrin matrix doped with a GF-loaded, phase-shift emulsion. The GF is released when the ARS is exposed to suprathreshold ultrasound via a mechanism termed acoustic droplet vaporization. In this study, we investigate how different spatial patterns of suprathreshold ultrasound can impact the biological response upon in vivo implantation of an ARS containing basic fibroblast growth factor (bFGF). ARSs were fabricated with either perfluorohexane (bFGF-C6-ARS) or perflurooctane (bFGF-C8-ARS) within the phase-shift emulsion. Ultrasound generated stable bubbles in bFGF-C6-ARS, which inhibited matrix compaction, whereas transiently stable bubbles were generated in bFGF-C8-ARS, which decreased in height by 44% within one day of implantation. The rate of bFGF release and distance of host cell migration were up to 6.8-fold and 8.1-fold greater, respectively, in bFGF-C8-ARS versus bFGF-C6-ARS. Ultrasound increased the formation of macropores within the fibrin matrix of bFGF-C8-ARS by 2.7-fold. These results demonstrate that spatially patterning suprathreshold ultrasound within bFGF-C8-ARS can be used to elicit a spatially-directed response from the host. Overall, these findings can be used in developing strategies to spatially pattern regenerative processes. Statement of Significance: Hydrogels are commonly used in regenerative medicine for the delivery of growth factors (GFs). The spatial and temporal presentations of GFs are critical for directing regenerative processes, yet conventional hydrogels do not enable such control. We have developed a composite hydrogel, termed an acoustically-responsive scaffold (ARS), where GF release is non-invasively and spatiotemporally-controlled using focused ultrasound. The ARS consists of a fibrin matrix doped with a phase-shift emulsion loaded with GF, which is released when the ARS is exposed to ultrasound. In this in vivo study, we demonstrate that spatially patterning ultrasound within an ARS containing basic fibroblast growth factor (bFGF) can elicit a spatially-directed response from the host. Overall, these findings can be used in developing strategies to spatially pattern regenerative processes. Graphical abstract: Image, graphical abstract